PEMAKNAAN PUISI â€œSITI SURABAYAâ€ KARYA F. AZIZ MANNA PENDEKATAN NEO-HISTORISISME - Muhri, Muhri (Program Studi Pendidikan Bahasa Indonesia STKIP-PGRI Bangkalan, 2021)
This study aims to interpret poetry with structural and semiotic meanings. The approach to meaning is influenced by the content aspect that talks about the history of Surabaya with an adequate historical understanding. With this background the approach used is the Neo-Historicism approach which seeks to interpret literary works from a historical perspective. The main data of this research is the poem â€œSiti Surabayaâ€ by F. Aziz Manna. Secondary data is in the form of scientific writings in the form of books, research results, media articles both print and electronic as interpreting texts. From the results of the analysis, it can be described that the poem discusses Surabaya in three eras, namely the Majapahit era, the Dutch colonial era, and the independence era.